Control of histone H3 phosphorylation by CaMKIIδ in response to haemodynamic cardiac stress. Issue 4 (17th December 2014) - Awad, Salma; Al‐Haffar, Kamar Mohamed Adib; Marashly, Qussay; Quijada, Pearl; Kunhi, Muhammad; Al‐Yacoub, Nadya; Wade, Fallou S; Mohammed, Shamayel Faheem; Al‐Dayel, Fouad; Sutherland, George; Assiri, Abdullah; Sussman, Mark; et al.
Abstract Heart failure is associated with the reactivation of a fetal cardiac gene programme that has become a hallmark of cardiac hypertrophy and maladaptive ventricular remodelling, yet the mechanisms that regulate this transcriptional reprogramming are not fully understood. Using mice with genetic ablation of calcium/calmodulin‐dependent protein kinase II δ (CaMKIIδ), which are resistant to pathological cardiac stress, we show that CaMKIIδ regulates the phosphorylation of histone H3 at serine‐10 during pressure overload hypertrophy. H3 S10 phosphorylation is strongly increased in the adult mouse heart in the early phase of cardiac hypertrophy and remains detectable during cardiac decompensation. This response correlates with up‐regulation of CaMKIIδ and increased expression of transcriptional drivers of pathological cardiac hypertrophy and of fetal cardiac genes. Similar changes are detected in patients with end‐stage heart failure, where CaMKIIδ specifically interacts with phospho‐H3. Robust H3 phosphorylation is detected in both adult ventricular myocytes and in non‐cardiac cells in the stressed myocardium, and these signals are abolished in CaMKIIδ‐deficient mice after pressure overload. Mechanistically, fetal cardiac genes are activated by increased recruitment of CaMKIIδ and enhanced H3 phosphorylation at hypertrophic promoter regions, both in mice and in human failing hearts, and this response is blunted in CaMKIIδ‐deficient mice under stress. We also document that the chaperone protein 14–3–3 binds phosphorylated H3 in response to stress, allowing proper elongation of fetal cardiac genes by RNA polymerase II (RNAPII), as well as elongation of transcription factors regulating cardiac hypertrophy. These processes are impaired in CaMKIIδ‐KO mice after pathological stress. The findings reveal a novel in vivo function of CaMKIIδ in regulating H3 phosphorylation and suggest a novel epigenetic mechanism by which CaMKIIδ controls cardiac hypertrophy. © 2014 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.